The propensity for money laundering amongst accountants in Malaysia / Nur Hanie Johari, Wan Nailah Abdullah and Hasnisah Hassan - Johari, Nur Hanie; Abdullah, Wan Nailah; Hassan, Hasnisah (Research Management Centre (RMC), 2023)
Based on the International Narcotics Control Strategy Report, Malaysia is used as a transit country to move drugs globally. Launderers continuously update their new routes for laundering their illegal funds. Accountants are vulnerable to involvement in money laundering as they are the gatekeepers and the bridge to committing money-laundering activities. This paper conceptualises the relationship between the propensity for money laundering amongst accountants in Malaysia, with their familiarity with the Financial Action Task Force (FATF), the Anti-Money Laundering, Anti-Terrorism Financing and Proceeds of Unlawful Activities (AMLATFAPUAA) Act 2001, and the Anti-Money Laundering (AML) Requirements.